Mechanical Characteristics of Aluminum Metal Matrix Composite Fabricated by Powder Metallurgy: A Review - Kumaraswamy, H. S.; Barath, V.; Krishna Rao, T. (Asian Review of Mechanical Engineering, 2018)
The mechanical properties of composites are mainly depends on the distribution of reinforced particles into the matrix material. The distribution of particles plays a very important role while manufacturing the composite. To achieve good mechanical properties, uniform distribution of reinforcement into the matrix is very important, present review reveals one of the manufacturing methods to achieve uniform distribution of particle and to investigate the mechanical properties. There are several types of manufacturing methods are there for the composites, Powder metallurgy is one of the method to manufacture the composites, uniform mixing of particles can achieved by this technique and also the porosity is decreased in this technique but comparatively costlier than the stir casting technique. The present study also reveals a study on different mechanical & tribological characteristics of aluminum metal matrix composite reinforced with different material like silicon carbide, boron carbide, fly ash, tungsten carbide etc. manufactured by powder metallurgy technique.